Plan estratégico de la Cooperativa de ahorro y crédito Atuntaqui Ltda., para el impulso del emprendimiento de socios y pequeñas y medianas empresas. - Vallejo, Evelyn A. (2022)
One of the challenges that entrepreneurs currently face is the restriction to access financing for reasons such as payment capacity, interest rate and a low diversity of credit products and a series of requirements that cannot be met, for this reason this research aims to design a strategic plan that benefits the Cooperativa de Ahorro y Crédito "Atuntaqui" and even entities of similar characteristics, This is why this research aims to design a strategic plan that will benefit the "Atuntaqui" Savings and Loan Cooperative and even similar entities, providing members with products that meet their needs with affordable interest rates and more agile credit qualification procedures supported by the technological support of the virtual cooperative and the mobile application, facilitating the financial management of the members, optimizing their time and economic resources; to carry out this research, it was decided to request the support of the workers in the credit area through surveys, interviews with business personnel to know the criteria of the people who work directly with members and future clients, know their needs and have proposals for new credit products, there was relevant information based on the concepts of various authors and its veracity will be seen in the bibliographical references; As a result of this research, it became evident that there is a growing need for credit products for members who are part of the medium and small business sector, as well as entrepreneurs, since the Cooperative does not have specific products for them, for this reason it is necessary to make a strategic plan for the entity.